THE INTERSECTION BETWEEN PTSD AND COMORBID DISORDERS:IMPLICATIONS FOR DIAGNOSIS AND TREATMENTS - Griffiths, Gareth (E-Journal VFU, 2025)
Post-Traumatic Stress Disorder (PTSD) frequently co-occurs with depression, anxiety disorders, and substance use disorders, complicating diagnosis and treatment. This article explores the bidirectional relationships between PTSD and its comorbidities, focusing on psychological, biological, and social dimensions. By reviewing current literature and theoretical models, it emphasizes the need for integrated care approaches tailored to the multifaceted nature of these conditions. The findings advocate for holistic, patient-centered interventions that address overlapping symptoms and root causes, moving beyond conventional one-size-fits-all treatments.